ANALYSIS OF THE RELATIONSHIP BETWEEN THE SOCIAL REPRESENTATION AND THE INDIVIDUAL BODY COMPOSITION - Trofin Petrut-Florin; Abalasei Beatrice; Honceriu Cezar; Drosescu Paula; Cojocariu Adrian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The objective of our study is to pinpoint the relationship between perceived image in social setting and the image determined by physical development indices. Representations are generated by members of a group, thus being part of its structure, but this structure can be far from reality, which says something about the diversity and complexity of taking over propagated messages. Hence, our hypothesis is that the social representation of the individual is influenced by certain body composition indices. We included 28 male volunteers in our study, aged between 19 and 30. The findings and their analysis attest that the body image model of subjects' body, obtained in the social setting pertaining to the statistical population of our sample, is correlated with both their body mass and their body mass index.